2008
DOI: 10.1111/j.1471-4159.2008.05611.x
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extracts interfere with the stress‐protective activity of PrPC and the formation of PrPSc

Abstract: A hallmark in prion diseases is the conformational transition of the cellular prion protein (PrPC) into a pathogenic conformation, designated scrapie prion protein (PrPSc), which is the essential constituent of infectious prions. Here, we show that epigallocatechin gallate (EGCG) and gallocatechin gallate, the main polyphenols in green tea, induce the transition of mature PrPC into a detergent‐insoluble conformation distinct from PrPSc. The PrP conformer induced by EGCG was rapidly internalized from the plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 56 publications
1
81
0
Order By: Relevance
“…It is therefore also feasible that EGCG has the capacity to break up pre-formed fibrils; this would support our findings of attenuated toxicity of PC12 cells when incubated with pre-formed fibrillar Ab protein together with EGCG, and the results of the TEM experiments where preformed fibril and aggregate formation was directly disrupted by EGCG. This remarkable property of EGCG is a finding similarly observed for both amyloid-b and a-synuclein in EGCGtreated PC12 cells (Bieschke et al, 2010) and for other forms of pathogenic amyloid-b proteins (Chandrashekaran et al, 2010;Hauber, Hohenberg, Holstermann, Hunstein, & Hauber, 2009;Rambold et al, 2008). EGCG also displays anti-amyloid efficacy following in vivo oral dosing, suggesting it has a favourable bioavailability to act as an orally available amyloid-b fibril-disrupting agent (Lee et al, 2009).…”
Section: Discussionmentioning
confidence: 59%
“…It is therefore also feasible that EGCG has the capacity to break up pre-formed fibrils; this would support our findings of attenuated toxicity of PC12 cells when incubated with pre-formed fibrillar Ab protein together with EGCG, and the results of the TEM experiments where preformed fibril and aggregate formation was directly disrupted by EGCG. This remarkable property of EGCG is a finding similarly observed for both amyloid-b and a-synuclein in EGCGtreated PC12 cells (Bieschke et al, 2010) and for other forms of pathogenic amyloid-b proteins (Chandrashekaran et al, 2010;Hauber, Hohenberg, Holstermann, Hunstein, & Hauber, 2009;Rambold et al, 2008). EGCG also displays anti-amyloid efficacy following in vivo oral dosing, suggesting it has a favourable bioavailability to act as an orally available amyloid-b fibril-disrupting agent (Lee et al, 2009).…”
Section: Discussionmentioning
confidence: 59%
“…As with any such phenotypic screening follow-up cascade, elucidating the precise mechanism of action required the development of several specific and general assays that flag spurious promiscuous binders. This was exemplified by the two natural trihydroxyphenyl compounds from tea that have been linked to a number of health benefits through their interactions with various protein targets (Mori et al, 2010;Palhano et al, 2013;Rambold et al, 2008). Autooxidation of the gallyl and gallate moieties within EGCG and TG can create reactive species that react with cysteine thiol groups (Ishii et al, 2008) and/or free amines in proteins (Palhano et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Alzheimer | Parkinson | catechine | misfolding | oligomer P revious studies have shown that the polyphenol (-)-epi-gallocatechine gallate (EGCG), found in large amounts in green tea, has antiamyloidogenic properties and modulates the misfolding of disease proteins and prions (1)(2)(3)(4)(5). EGCG directly binds to unfolded polypeptide chains and inhibits β-sheet formation, an early event in the amyloid formation cascade (6).…”
mentioning
confidence: 99%